Quality assurance audit in adult cardiac anaesthesia - Syed Shabbir Ahmed; Mohammad Hamid; Faisal Junejo (Journal of the Pakistan Medical Association, 2020)
Objective: To observe and assess different anaesthesia related quality indicators during adult cardiac surgery. Study design: Clinical audit report. Place and duration of study: The aga khan university hospital karachi, Pakistan, from October 2016 to March 2017. Methodology: Data were collected prospectively from all 264 patients scheduled for cardiac surgery and observe different indicators in pre-induction, pre cardiopulmonary bypass (CPB) period, on CPB, post CPB period and transfer from operating room to cardiac intensive care unit. Results: Total 217 patients included in the study, our compliance of documentation was found to be 82.19%. In pre-induction phase, difficult intravenous and invasive line access in 42 patients (19.3%). Inadvertent Carotid puncture occurred in 7 patients (3.2%) during central venous access. Cardiac arrhythmias were found in 19 patients (8.8%). Inappropriate information in preoperative form found in 6 patients (2.8%). Drug reactions (only rashes) were noted in 4 patients (1.8%). Preoperative drugs for anxiolysis used in 145 patients (66.8%). Ramsey sedation score-2 was found in majority of our patients 100(69%), while Ramsey score-3 was documented only in 22 patients (15.2%). Haemodynamic instability (32 patients) and difficult intubation (17 patients) were main pre-bypass indicators. Haemodynamic issues were again significant in CPB period 15(6.9%). CPB difficulties were seen in 8 (3.6%) patients, which includes unplanned use of inotropic support, prolonged CPB wean off procedure, insertion of IABP post CPB and more than one attempt at CPB weaning included. In post CPB period abnormal ACT was found in 17 patients (7.8%), while haemodynamic instability Continuous...